2020
DOI: 10.1111/gbb.12696
|View full text |Cite
|
Sign up to set email alerts
|

The effect of background strain on the behavioral phenotypes of the MDGA2+/− mouse model of autism spectrum disorder

Abstract: The membrane‐associated mucin (MAM) domain containing glycosylphosphatidylinositol anchor 2 protein single knock‐out mice (MDGA2+/−) are models of ASD. We examined the behavioral phenotypes of male and female MDGA2+/− and wildtype mice on C57BL6/NJ and C57BL6/N backgrounds at 2 months of age and measured MDGA2, neuroligin 1 and neuroligin 2 levels at 7 months. Mice on the C57BL6/NJ background performed better than those on the C57BL6/N background in visual ability and in learning and memory performance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 118 publications
(174 reference statements)
1
11
1
Order By: Relevance
“…Surprisingly, deletion of only MDGA1 resulted in a modest reduction in mIPSC amplitude as well as in a decreased size of VIAAT and GABAARg2 puncta size, in stark contrast to the increase in mIPSC frequency and symmetric synapse density previously reported in area CA1 (24). The reason for this discrepancy most likely lies in differences in the strain background (C57BL/6JRj in our study, mixed C57BL/6NxJ in Connor et al (24)), which has previously been shown to modulate both MDGA2 function (52) and GABAARa2 expression (53). Importantly, our findings of a reduction of GABAergic synapse markers and smaller mIPSC amplitude are internally consistent, and our observation of a prominent reduction of sIPSC and mIPSC frequency and amplitude, as well as gephyrin and GABAARg2 staining intensity in the Nlgn2 KO, are consistent with previous findings (10), validating our technical approach.…”
Section: Discussioncontrasting
confidence: 84%
“…Surprisingly, deletion of only MDGA1 resulted in a modest reduction in mIPSC amplitude as well as in a decreased size of VIAAT and GABAARg2 puncta size, in stark contrast to the increase in mIPSC frequency and symmetric synapse density previously reported in area CA1 (24). The reason for this discrepancy most likely lies in differences in the strain background (C57BL/6JRj in our study, mixed C57BL/6NxJ in Connor et al (24)), which has previously been shown to modulate both MDGA2 function (52) and GABAARa2 expression (53). Importantly, our findings of a reduction of GABAergic synapse markers and smaller mIPSC amplitude are internally consistent, and our observation of a prominent reduction of sIPSC and mIPSC frequency and amplitude, as well as gephyrin and GABAARg2 staining intensity in the Nlgn2 KO, are consistent with previous findings (10), validating our technical approach.…”
Section: Discussioncontrasting
confidence: 84%
“…Our study had some limitations, such as experiments in single‐sex cohorts, lack of uniform mouse background and very modest sample size in some cohorts. Sex‐ and background‐specific effects have been described for genetic mouse models of ASD and ID 62‐67 . Therefore, to confirm and extend our present findings in mice with mutations in Syngap1 , Nlgn3 , Dlgap1 , Dlgap2 and Shank2 , future behavioural experiments involving larger sized cohorts comprising both males and females would be advantageous.…”
Section: Discussionsupporting
confidence: 82%
“…Second, the robustness of the genetic modification on learning and memory, independent of genetic background, can be established by testing the same genetic modification on different background strains. Phenotypes that differ across genetic backgrounds may reveal epsistatic interactions, or the masking/exaggeration of behavioral phenotypes due to pre‐existing differences in the behavior of background strains 54,55,106,107 . Therefore, it is important to conduct comprehensive analyses of behavioral phenotypes within background strains used 53,57,62,108–111 .…”
Section: Discussionmentioning
confidence: 99%